Participation in school‐related activities that require hand use for children with and without developmental disabilities. Issue 3 (18th December 2017) - Cho, M.; Rodger, S.; Copley, J.; Chien, C.‐W.
Abstract: Background: Children with developmental disabilities (DD) may experience limited participation in school activities. Little is known about whether school participation of children with DD who attend special schools is impacted. This study specifically focused on physical engagement in school‐related activities that require hand use for the comparison between this group of children with DD and typically developing children. Methods: The sample consisted of 97 children with DD who attended special schools (mean age 8.2 ± 2.9 years; 60 boys and 37 girls) and 105 typically developing children who attended mainstream schools/kindergartens (mean age 8.6 ± 2.4 years; 48 boys and 57 girls). Parents completed the Children's Assessment of Participation with Hands, one of the domains of which captures participation in eight school‐related activities involving hand use. Results: Parents of children with DD reported that their children participated less, in terms of the number ( χ 2  = 8.45–14.97, P  ≤ 0.004) and frequency ( t  = 4.00–6.47, P  < 0.001), in four activities than typically developing children. Parents of children with DD also reported that more assistance was needed for their children's participation in all activities ( t  = 6.93–11.92, P  < 0.001), and they wanted their children to participate in most activities more often and more independently ( χ 2  = 18.46–59.34, P  < 0.001). Conclusions: Differences in participation in school‐related activities requiring hand use between children with DD and typically developing children were revealed generally across all participation dimensions (does participate, frequency, independence, and desired change). This study provides information on the areas in which greater efforts are needed to support children's school participation.